Hubungan Antara Profesionalitas konselor dan Kepuasan siswa dalam Pelayanan Konseling di Sekolah - Andrian Bimantara (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2021)
This research was motivated by the results of a short interview with Muhammadiyah Wonosobo high school students with 75% of the results stating that they were not satisfied with the counseling services at the school. The purpose of this study is to determine the relationship between the professionalism of the counselor and student satisfaction in counseling services. This research is a correlational study with 117 samples from 330 populations, which were obtained using purposive sampling. Data collection was obtained with a counselor professional scale questionnaire and a student satisfaction scale questionnaire. The scale validity coefficients are 0.257-0.594 and 0.033-0.508 with croanbach alpha values 0.732 and 0.915. The data analysis technique used is Pearson Correlation Product Moment. The results show that there is a significant relationship between counselor professionalism and student satisfaction with the product moment correlation coefficient value of 0.016 (r = 0.016, p≥0.05). In the research that researchers conducted, there were differences in results where the high level of